2021
DOI: 10.1016/j.cma.2021.114005
|View full text |Cite
|
Sign up to set email alerts
|

Blended isogeometric Kirchhoff–Love and continuum shells

Abstract: The computational modeling of thin-walled structures based on isogeometric analysis (IGA), non-uniform rational B-splines (NURBS), and Kirchhoff-Love (KL) shell formulations has attracted significant research attention in recent years. While these methods offer numerous benefits over the traditional finite element approach, including exact representation of the geometry, naturally satisfied high-order continuity within each NURBS patch, and computationally efficient rotation-free formulations, they also presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…(Studies on layered structures based on various thickness assumptions can be found in Refs. [44][45][46][47][48][49][50].) For pinned-pinned and fixed-fixed boundary conditions, these trial functions are written as…”
Section: Solution Proceduresmentioning
confidence: 99%
“…(Studies on layered structures based on various thickness assumptions can be found in Refs. [44][45][46][47][48][49][50].) For pinned-pinned and fixed-fixed boundary conditions, these trial functions are written as…”
Section: Solution Proceduresmentioning
confidence: 99%
“…The number of layers, thickness and direction are exactly the same, the boundary conditions are the same, and the applied loads are all the cutting force of 100 N/mm, the opening area is the same, both are 10000 mm². The web models of triangular, rhombic and circular open beams were established for simulation analysis [16].…”
Section: The Influence Of Different Opening Shapesmentioning
confidence: 99%
“…Over the past few years, many IGA based Kirchhoff-Love rectangular shell elements [2,12,14,37,40,41] have been proposed. However, the application of these elements is limited because a single B-spline/NURBS patch can only represent the surfaces of rectangular topological type.…”
Section: Introductionmentioning
confidence: 99%